Quantitative imaging of magnetization transfer using multiple selective pulses. - Gochberg, D; Kennan, R; Robson, M; Gore, J (1999)
New spectroscopic and imaging methods have been developed for quantitatively measuring magnetization transfer (MT). These methods use trains of radiofrequency (rf) pulses with pulse separations much longer than 1/k(mf) and pulse durations much shorter than 1/k(mf), where k(mf) is the rate of MT from the immobile (macromolecular) protons to the mobile (free water) protons. Signal sensitivity to MT occurs when these pulses affect the mobile and immobile proton pools to different degrees. The signal from water may be quantitatively related to the macromolecular content of the sample using theory. The method has been used to make quantitative measurements of macromolecular content in cross-linked bovine serum albumin and employed in conjunction with echoplanar imaging to produce maps of the spatial distribution of the macromolecular content.